Temporal trends, characteristics and comorbidities of patients with hypertrophic cardiomyopathy in Denmark from 2005 to 2018: a nationwide cohort study. (3rd October 2022) - Zoerner, C R; Pallisgaard, J L; Schjerning, A M; Toennesen, J; Jensen, M K; Gislason, G; Hansen, M L
Abstract: Background: The majority of patients with Hypertrophic cardiomyopathy (HCM) are mildly symptomatic or unaware of their condition, but some develop serious complications such as heart failure, atrial fibrillation (AF) as well as sudden cardiac death. Previous studies have suggested that HCM detection-rates in women are significantly lower than in men. This leads to diagnosis often being delayed to later stages of the disease in women, where symptoms are more severe. Further characterization of HCM patients to improve early detection of adverse outcomes and warning signs might improve long-term outcomes. Purpose: To describe the characteristics of Danish patients diagnosed with HCM between 2005–2018 and determine trends and changes in these factors over time. Methods: All patients aged 16 years or older with a diagnosis of HCM between the 1st of January 2005 and the 31st of December 2018 were identified in Danish nationwide administrative registers and included in the study. Time trends were calculated, and differences analyzed using the Cochran-Armitage trend test and linear regression. Results: A total of 3856 patients were diagnosed with HCM in the study period and included in the study. The median age at diagnosis was 68 years (IQR 56 and 78 years), 53% were male, and 44% were diagnosed with obstructive HCM, while the number of patients diagnosed with HCM each year overall increased. At the time of diagnosis, 22, 3% patients were previously diagnosed with ischemic heart disease, 17% with AF, 7, 5% with ischemic stroke, 13, 6% with heart failure. Median age and gender distribution remained stable over time, while the proportion of obstructive HCM among the newly diagnosed decreased (p = <0.001) (Figure1). During the study period, there was a significant decrease in the prevalence of heart failure (p = <0.001), ischemic heart disease (p = <0.001), and chronic obstructive pulmonary syndrome (p = <0.001), while the prevalence of AF, hypertension and ischemic stroke remained stable (Figure 2). Conclusion: Despite previous studies describing a gender gap in patients diagnosed with HCM, gender distribution was near equal in this cohort. The number of patients diagnosed with non-obstructive HCM is increasing and the prevalence of comorbidities such as heart failure, ischemic heart disease, and COPD decreased over time. Whether these findings are the result of improved early detection of HCM warrants further research and examination. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Herlev-Gentofte Hospital, Denmark